Surgical Outcome and extent of resection in Endoscopic Endonasal Transphenoidal excision of Pituitary Tumor - Gautam, Subodh; Kolakshyapti, Manish; Siddiqui, Saharoj; Nepal, Ashmita (Nepal Journal of Neuroscience, 2025)
Introduction: Pituitary adenomas are common benign tumors located intracranially that arises from the pituitary gland. Depending on their size and endocrine function of the tumor, they can be either asymptomatic or present with symptoms due to hormonal dysfunction or compression of nearby structures. Among the various surgical approaches that exist for the management of pituitary adenomas, the endoscopic endonasal transsphenoidal approach is a widely used technique. The study evaluates the surgical outcomes and extent of tumor resection using this approach. Materials and Methods: The study was conducted at Bir Hospital, Kathmandu, Nepal, which included 38 study participants with pituitary macroadenomas. A non-probability sampling method was used. Results: The most common presenting symptom was visual defects (57.8%), followed by headaches (31.5%) and galactorrhea (26.3%). Preoperative Knosp grading revealed 26.3% of cases as grade 0, 39.5% as grade 1, 21.1% as grade 2, and 13.2% as grade 3. Postoperatively, 78.9% of patients had complete tumor excision. Significant improvement in visual acuity was observed, with 21.1% achieving 6/9 vision in the right eye and 23.7% in the left eye. However, two patients showed no perception of light both pre- and post-operatively. The hormonal level decreased significantly post operatively. Conclusion: Pituitary adenomas often present late, leading to visual and endocrine impairment. The visual and endocrine improvement of the patient was significant following the Endoscopic endonasal transsphenoidal surgery, with most patients achieving complete tumor excision. Surgical outcomes at our center are comparable to existing data.